Indeks Paham dan Sikap Keagamaan Mahasiswa di Universitas Islam Negeri Alauddin Makassar - Abdullah, Abdullah (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2017)
The article attempts to measure ideological preference and religious attitude of the students of Alauddin State Islamic University (UIN) Makassar. The typology of religious understanding is categorized into radical, moderate, and liberal. These three typologies help us to observe preference indicators based on students? responses to four categorical variables, namely Islam and religious pluralism, formalization of Islam (relation of religion and state), Islam and intellectual discourse, and perception of jihad and religious violence. Employing quantitative approach, the author tries to measure the level of religious preferences of UIN Alauddin?s students within positivistic paradigm by organizing the data into a pattern, category, and basic unit description. The study finds that the level of preference of four variables and 16 questions asked to the students of UIN Alauddin shows us index result 2.76 or moderate category. However, it is also found that there has been potential preference, within the same time, into radical attitude. The reason is that in some variables I find shocking index numbers, which are close to radical verge as it can be seen in the variables of Islam and pluralism and the formalization of Islam which reach the index 2.49 and 2.40 respectively. Keywords: ; religious attitude; radical; moderate; liberal.